2021
DOI: 10.3390/coatings11111428
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Influence of Annealing on Microstructure and Mechanical Properties of Electrodeposited Ni-Mo and Ni-Mo-W Alloy Coatings

Abstract: Ni-Mo and Ni-Mo-W coatings were electrodeposited on a stainless steel sheet, and then were annealed at 200, 400, and 600 °C. The effect of annealing heat treatment on the microstructure of Ni-Mo and Ni-Mo-W electrodepositions, their nano-hardness, and tribological properties were investigated. It was revealed that the average crystalline are refined and phase separation are promoted with formation of Mo-W related intermetallic precipitates at temperature exceed 400 °C on account of the co-existence of Mo-W ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This also affects the kinetics of the reaction between the carbon precursor (CH4) and the Ni catalyst layer, thereby influencing the efficient amount of carbon atoms absorbed and incorporated into the catalyst layer. In addition, a longer time and higher temperature during the annealing process can result in the rate of atomic diffusion in the material layer being slower, resulting in a more significant reduction in the atomic element content of a material [33,34], which also affects precursor atomic interactions. CH4 with Ni as the catalyst layer [23].…”
Section: Energy Dispersive X-ray Spectroscopy (Eds) Analysismentioning
confidence: 99%
“…This also affects the kinetics of the reaction between the carbon precursor (CH4) and the Ni catalyst layer, thereby influencing the efficient amount of carbon atoms absorbed and incorporated into the catalyst layer. In addition, a longer time and higher temperature during the annealing process can result in the rate of atomic diffusion in the material layer being slower, resulting in a more significant reduction in the atomic element content of a material [33,34], which also affects precursor atomic interactions. CH4 with Ni as the catalyst layer [23].…”
Section: Energy Dispersive X-ray Spectroscopy (Eds) Analysismentioning
confidence: 99%
“…In addition, heat treatment can be applied to further improve the hardness and wear resistance of the obtained coatings [3,[16][17][18]. Wang et al reported that the suitable annealing can significantly enhance the properties and microstructure of Ni-W/diamond composite coatings [16].…”
Section: Introductionmentioning
confidence: 99%